PEMETAAN KETAHANAN PANGAN REGIONAL DI JAWA TIMUR - Sugeng Raharto (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2010)
The problem of food security in Indonesia is exacerbated by the high number of poverty in Indonesia. This is exacerbated by the high dependence of the Indonesian rice consumption has increased and the national rice production has decreased. The research objective is to map the village level food security based on the aspects of availability, aspects of food access and livelihoods and access to nutritional health. Methods of determining district purposively sample while the determination of villages using a Multistage Sampling. The study was conducted in Sidoarjo Regency as a regional industrial center, Jember regency as agricultural centers and Banyuwangi Regency as fishery centers.Results obtained from this study are: (1) The villages in Sidoarjo regency 60% in the category of food resistant, and 40% in the category of food insecurity. (2) The villages in Jember regency 57% in the category of food resistant and 43% in the category of food insecurity. (3) Villages Banyuwangi 72% in the category of food resistant and 28% in the category of food insecurity.Key words: mapping, regional, hold food, food security.